Classical Mythology for Teachers of English - Mayerson, Philip ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
A knowledge of the major myths and legends will be an invaluable asset to the student in acquiring a richer and deeper appreciation of his reading, be t in English or a foreign language. The teacher must treat the material systematically, starting with the creation of the primal power out of chaos and the struggles for power which ultimately lead to the victory of Zeus and the Olympians over the Titans. The teacher then proceeds one by one through the gods of the heavens, the Twelve Olympians, and goes from there beneath the earth to explore the topography of the Underworld and the lore of the gods of death. Like the gods, the heroes should be treated genealogically, house-by-house or family-by-family. Back-up texts for the teacher include: H. J. Rose's "A Handbook to Greek Mythology,""Oxford Classical Dictionary,""Crowell's Handbook of Classical Mythology," and "Classical Mythology: An Annotated Bibliographical Survey." (LL)
ERIC Note: Paper presented at the Annual Meeting of the National Council of Teachers of English (63rd, Philadelphia, November 22-24, 1973).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classical Literature; English Curriculum; English Education; English Instruction; Liberal Arts; Literature Appreciation; Literature Guides; Mythology; Undergraduate Study